Politeness Strategy in Shanghai Knights Film - Ernovilinda Ernovilinda (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
Language is a communication tool for every human being and is used to convey ideas, messages, intentions, feelings, opinions to others or even to meet daily needs. Intercultural communication is a communication that frequently occurs in the community. Pragmatics is a branch of linguistics that discusses aspects of language as a communication tool. When combined with culture, intercultural communication that occurs in society can be understood. In order for a speaker's language to be accepted in a society, he needs to fully understand the rules that apply in that society, including an understanding of the appropriate use of certain language functions or speech acts. There is a close relationship between pragmatics and the concept of politeness. Politeness is fundamental in pragmatics because this is a universal phenomenon in the use of language in social contexts. The focus of this research is to identify the politeness strategies used by the two main characters in the Shanghai Knights film, Chon Wang and Roy O'Bannon, and analyze them in terms of the cultural background of the two main characters. This is a qualitative descriptive study. The results show that the politeness strategy used is strongly influenced by their cultural background. The strategy used most often is the bald-on record strategy while the Off-record politenses strategy is the strategy that is the least used by the two main characters of the film. This suggests that an understanding of politeness strategies is needed to realize face-threatening actions (FTA). In other words, politeness strategies are used to maintain continuity and success in communicating.